2016
DOI: 10.1021/acsami.6b13926
|View full text |Cite
|
Sign up to set email alerts
|

Facile Functionalization of Polymer Surfaces in Aqueous and Polar Organic Solvents via 3-Mercaptopropylsilatrane

Abstract: Surface modification of a polymer substrate with a mercapto functionality is crucial in many applications such as flexible circuitry and point-of-care biosensors. We present here a novel bifunctional molecular adhesive, 3-mercaptopropylsilatrane (MPS), as an interface between polymer and metal surfaces. Under ambient conditions, surface modification of polymer surfaces with a mercapto functionality can be achieved with low concentration (0.46 mM) of MPS in aqueous solvent (50% ethanol) in a short time (<30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Furthermore, research also focuses on the functionalization of macromolecules (Tseng et al, 2016; Cao et al, 2018; Wu et al, 2018). Although methods for macromolecule modification are numerous, a flexible, moderate, and a reliable reaction is still an effective and efficient method of polymer modification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research also focuses on the functionalization of macromolecules (Tseng et al, 2016; Cao et al, 2018; Wu et al, 2018). Although methods for macromolecule modification are numerous, a flexible, moderate, and a reliable reaction is still an effective and efficient method of polymer modification.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous linker 11‐mercaptoundecanoic acid can grab the noble metal surface through a sulfur bond and immobilize the amino groups of biomolecules via the EDC/NHS system (EDC represents 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide hydrochloride and NHS represents N‐hydroxysuccinimide) . Another molecule, 3‐mercaptopropylsilatrane, can also serve as a linker at the interface between polymer and metallic surfaces …”
Section: Principle and Fabrication Of Lspr Biosensorsmentioning
confidence: 99%
“…It has been shown that silatrane coatings, in contrast to alkoxysilane ones, ensure a more facile formation of thin and uniform films, as well as better molecular regularity and availability of the functional groups on the various surfaces (glass, mica, paper, cotton, natural and synthetic polymers, silica gels, metal oxides) (see Refs. [ 24 , 25 , 26 , 27 , 28 ] and literature cited therein).…”
Section: Introductionmentioning
confidence: 99%